Mothers at Peace: International Peacebuilding and Post-conflict Fertility - Vincenzo Bove; Jessica Di Salvatore; Leandro Elia; Roberto Nistico (Institute of Labor Economics (IZA), 2023)
A considerable body of empirical evidence indicates that conflict affects reproductive behaviour, often resulting in an increased fertility rate due to higher child mortality and limited access to healthcare services. However, we know much less about the effect of peace in a post-conflict setting. This study explores how the external provision of security affects fertility by focusing on the UN intervention in Liberia. Combining DHS birth history data with information on road distance to UN military compounds, we find that women living in the proximity of peacekeepers have lower fertility rates in the deployment period. This is due to parents prioritizing quality over quantity: peacekeepers improve maternal and child health and encourage family planning by enabling donors and humanitarian actors to deliver infrastructures and services and facilitating citizens' access to such services. We also provide evidence that UN mission revitalizes local economic activities, thus increasing the opportunity cost of childbearing.
Keywords: J16; J24; D74; F50; 330; conflict; fertility; maternal health; child health; UN operations